The Gambia : 2001 Article IV Consultation-Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Authorities of The Gambia. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2001)
The Gambia showed mixed economic performance. Executive Directors expressed concern about slippages in fiscal policy, which stemmed from the efforts to resolve the Alimenta property dispute and also from shortfalls in customs revenue, and delays in implementing some structural reforms. They encouraged the authorities to implement governance-strengthening measures for enhancing transparency and accountability in public resource management. They welcomed the antimoney laundering law, noted the progress made in improving economic and financial data, and stressed the need to tighten monetary and fiscal policies, and strengthen the financial sector.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet